The Usage Patterns of Credit/Debit Card across Various Demographics - Rauf, Arfat; Razi, Amir; Khalid, Afia; Hassan, Yasir (Pakistan Journal of Humanities and Social Sciences, 2022)
The purpose of this study was to assess the usage patterns of credit/debit cards across various demographic characteristics and to check their association with factors like card usage preferences, financial conditions, budget control, and money shortage. A close-ended questionnaire was used to record demographic information and responses to assess the comparative use of debit/credit cards in urban and rural areas of Lahore and Kasur. The estimated sample size was 225 consumers. After cleaning of data, the final sample analyzed consisted of 200 subjects. The empirical analysis was done through SPSS. The result shows that gender, occupation, area, and income play a significant role in the different usage patterns of credit/debit cards at the time of purchase.